A Case of Collision Tumor of MALT Lymphoma and Poorly Differentiated Adenocarcinoma Diagnosed Incidentally After Appendectomy for a Clinical Presentation of Acute Appendicitis. - T Kara; YY Karabulut; AR Bozdoğan; GE Yüksek (Journal of Clinical Case Reports and Images, 2019)
This report presents a case of collision tumors of low-grade B-cell lymphoma and poorly differentiated adenocarcinoma in the caceum of a 63-year-old woman. Lymphoma was diagnosed incidentally after appendectomy for a clinical presentation of acute appendicitis. Imaging follow-up demonstrated mesenteric lymphadenopathy and liver lesions, and all surgically resected regional mesenteric lymph nodes and liver biopsy were found to be infiltrated by both mucosa-associated lymphoid tissue (MALT) lymphoma and adenocarcinoma. Systemic chemotherapy was administered for advanced colonic adenocarcinoma with liver metastases. The occurrence of synchronous lymphoma and adenocarcinoma of the colorectal region is rare, and this is a previously unreported case of a patient that was diagnosed during management of acute appendicitis.
Keywords: Adenocarcinoma